2021
DOI: 10.3389/fnut.2021.644650
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Junk Food Consumption Among Adolescents in Pokhara Valley, Nepal

Abstract: Background: Junk food consumption and its consequences has become a major public health concern globally because of its deteriorating health consequences and surging prevalence. Though its adverse health consequences are widely prevalent in all age groups, children and adolescents are more at risk. It may lead to obesity and act as a risk factor for different non-communicable diseases (NCD's) like heart diseases, cardiovascular disease, cancer, hypertension, diabetes, etc. This study was carried out to explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 31 publications
2
40
1
1
Order By: Relevance
“…It was found that adolescents would not keep SSBs at home if they perceived disagreement from parents on SSB intake [ 32 ]. Furthermore, we found that availability of JFs in the home environment was directly and positively correlated with consumption of JFs among adolescents, which was in agreement with a previous study that suggested adolescents with higher frequent availability of JFs at home reported higher consumption of JFs [ 33 ]. This relationship was also found when studying the association between SSB intake and SSB availability in the home environment.…”
Section: Discussionsupporting
confidence: 92%
“…It was found that adolescents would not keep SSBs at home if they perceived disagreement from parents on SSB intake [ 32 ]. Furthermore, we found that availability of JFs in the home environment was directly and positively correlated with consumption of JFs among adolescents, which was in agreement with a previous study that suggested adolescents with higher frequent availability of JFs at home reported higher consumption of JFs [ 33 ]. This relationship was also found when studying the association between SSB intake and SSB availability in the home environment.…”
Section: Discussionsupporting
confidence: 92%
“…Our previous observations showing that PA intensity levels positively influenced healthy dietary pattern [25] represent encouraging results since those who practice vigorous PA began to adopt good eating habits that could last over time. This is in line with other studies [28,36,37] in which the increase in consumption of junk food, sweets, and candies are related to the habits of mainly sedentary adolescents. It was interesting to note that in our population sample, active adolescents display a better metabolic profile compared to sedentary adolescents in terms of LDL and insulin concentrations.…”
Section: Impact Of the Mediterranean Diet Food Choices On Metabolic P...supporting
confidence: 93%
“…The major factors contributing toward fast food consumption among adolescent is when they are outside the home. The incidence of fast-food consumption was higher in friend's company and on trip 11 . Lack of time and lifestyle were the least factors for fast-food consumption 11 .…”
Section: Introductionmentioning
confidence: 89%
“…The incidence of fast-food consumption was higher in friend's company and on trip 11 . Lack of time and lifestyle were the least factors for fast-food consumption 11 . Globally the incidence of fast-food consumption ranges from 60 to 70% 11,12 .…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation